Association between METS-VF and sarcopenia among middle-aged and older adults in China: The first longitudinal evidence from CHARLS - Tong Li; Yi Ren; Meilan Liu; Qing Wang; Tianhan Sun; Jianfu Cao; Hongyuan Cui (Experimental Gerontology)
Background: The association between the Metabolic Score for Visceral Fat (METS-VF) and sarcopenia remains unclear. This study aims to explore the relationship between METS-VF and sarcopenia in the middle-aged and older adults in China. Methods: Data were collected from 2011 and 2015 of the China Health and Retirement Longitudinal Survey (CHARLS) and 2948 participants were enrolled in this study. METS-VF was calculated using data from CHARLS. Sarcopenia was defined according to the criteria set by the Asian Working Group for Sarcopenia (AWGS) 2019. Potential confounders were identified through the Directed Acyclic Graph (DAG). The association between METS-VF and sarcopenia was then analyzed using multivariate logistic regression and restricted cubic spline (RCS) analysis. Results: Compared with low METS-VF, high METS-VF (OR = 1.65, 95 % CI = 1.08–2.52) showed a significant association with the occurrence of sarcopenia. Subgroup and interaction analyses revealed that residence (P for interaction = 0.012) influenced the relationship between METS-VF and sarcopenia. Additionally, RCS analysis demonstrated a non-linear relationship between METS-VF and sarcopenia. Conclusions: There is a positive non-linear correlation between METS-VF and sarcopenia with residence showing an impact on this association. Early identification of patients with possible sarcopenia by METS-VF is of great value for disease prediction, prevention, early diagnosis and timely treatment to reduce the potential disease burden.